1994
DOI: 10.1111/j.1432-1033.1994.tb18793.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of transferred nuclear‐Overhauser‐effect spectroscopy to measure the bound conformation of a disulphide‐replaced analogue of glutathione disulphide as an inhibitor of yeast glutathione reductase

Abstract: The analogue of glutathione disulphide (GSSG) in which the disulphide bridge of GSSG is replaced by -CH,-S-was synthesised from L-cystathionine using t-butoxycarbonyl and t-butyl ester protection with triethylsilane-promoted deprotection. This analogue (GCSG) was found to be a linear, competitive inhibitor of yeast glutathione reductase (K, value 981 pM at pH 7.0), a very poor substrate and not to act as an irreversible inhibitor of glutathione reductase. The weak binding of GCSG to glutathione reductase perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The similarity between sulfur and carbon in terms of both van der Waals radii and electronegativity has been commonly exploited in design of substrate analogs. In particular, alkyl sulfide derivatives of glutathione have been used to demonstrate specific substrate binding of thioltransferase/glutaredoxin (Hoog et al, 1982), while a methylene substitution for one of the sulfurs in the disulfide bridge of glutathione has been used to generate an inhibitor of glutathione reductase (Embrey et al, 1994).…”
mentioning
confidence: 99%
“…The similarity between sulfur and carbon in terms of both van der Waals radii and electronegativity has been commonly exploited in design of substrate analogs. In particular, alkyl sulfide derivatives of glutathione have been used to demonstrate specific substrate binding of thioltransferase/glutaredoxin (Hoog et al, 1982), while a methylene substitution for one of the sulfurs in the disulfide bridge of glutathione has been used to generate an inhibitor of glutathione reductase (Embrey et al, 1994).…”
mentioning
confidence: 99%
“…Although a number of chemical modifications have been performed on this molecule (Chen et al, 1986;Douglas, 1989;Xie et al, 1991;Embrey et al, 1994;GrOger et al, 1996), literature examination revealed that no data are available on GSH analogues containing a Cys residue replacing the C-terminal Gly and giving rise to a -Cys-Cys sequence.…”
Section: Introductionmentioning
confidence: 97%
“…Even for enzyme inhibitor design, a small change in the structure of an inhibitor can lead to major changes in the details of binding to the active site. This is lucidly illustrated for dihydrofolate reductase by the 180°twist found in the pteridine ring binding conformation for dihydrofolate compared to methotrexate (Matthews, 1978;Fontecilla-Camps, 1979), and the observation that simply replacing one sulfur atom of the disulfide bridge of GSSG by -CH2-(to give a -CH2S-bridge) leads to a major twist in the conformation accepted by the active site of glutathione reductase (Embrey et al, 1994). Experience in rationally designing ligands for DNA is considerably less than for proteins.…”
mentioning
confidence: 99%